Low back pain among children and adolescents - (:unkn) unknown (My University, 2004)
OBJECTIVES: We presented our experience with the diagnosis and treatment of low back pain in children. METHODS: We retrospectively reviewed 29 children (15 girls, 14 boys; mean age 12 years; range 9 to 17 years) who were treated for low back pain and had appropriate follow-ups. Etiologic causes were sought by clinical evaluation, radiologic studies, and laboratory tests. Patients with unknown etiology underwent symptomatic treatment. The mean follow-up period was 42 months (range 12 to 96 months). RESULTS: Etiology was determined in 26 patients (89%), which included spondylolysis/spondylolisthesis (n=8), Scheuermann's disease (n=6), neoplasia (n=5), discitis/vertebral osteomyelitis (n=4), and lumbar disc herniation (n=3). Spondylolysis was managed conservatively, except for one patient who had in situ spinal fusion for associated spondylolisthesis. Five patients with Scheuermann's disease were treated conservatively, while one patient required spinal fusion. Surgical treatment with biopsy, curettage, and bone grafting was performed for all neoplasias, but one which was followed-up conservatively. Two patients with discitis were managed with antibiotic treatment and two patients with vertebral osteomyelitis (Pott's abscess) underwent both medical treatment and surgical drainage and stabilization with strut graft. Lumbar disc herniation was treated conservatively in two patients, while one had surgical treatment with excision of disc fragments and limited laminectomy. Finally, all the patients became asymptomatic on final examinations. CONCLUSION: Serious consideration should be given to persistent low back pain in children. Clinical, radiologic, and laboratory findings can be elaborated into etiologic diagnoses and complete relief can be achieved with appropriate treatment.
Keywords: Female; Humans; Treatment Outcome; Turkey; Adolescent; Male; Child; Retrospective Studies; Radiography; Lumbar Vertebrae; Spinal Neoplasms; Intervertebral Disc Displacement; Medical Records; Spinal Diseases; Low Back Pain; Osteomyelitis; Scheuermann Disease; Spondylolysis